Penanaman Nilai Toleransi Pada Anak Melalui Sinema Animasi: Studi Analisis Karakter Tokoh Sinema Upin dan Ipin - Fakih Hamdani; Nurchamidah; Mohammed Elfadil Ahmed Bakhit (Indonesian Journal of Islamic Religious Education, 2025)
Attitudes and behaviors that do not accept differences can lead to intolerance in children, which is contrary to the core value of tolerance, which is acceptance and appreciation of differences. It is necessary to instill the value of tolerance so that tolerant attitudes continue to be maintained in children's attitudes and behaviors. One effort that can be made is through animated series, as children today are easily attracted to animated films due to their appealing visuals. This study examines the animated film Upin and Ipin by Moh Nizam Abdur Razak et al. This is a qualitative descriptive study using a literature review approach. Data collection techniques in this study used documentation and data analysis using content analysis techniques. The results of the study indicate that there are values of tolerance in the analysis of the characters in the animated film Upin and Ipin. These values of tolerance are accepting and respecting differences and can be categorized into religious tolerance and social tolerance. The attitude of tolerance, accepting and respecting differences, is an attitude that can be adopted and reflected by children in their daily lives through social interaction.